A composite carbon source for sewage treatment and preparation method thereof

By adopting a composite carbon source with a three-layer core-shell structure, the problem of insufficient carbon sources in traditional sewage treatment is solved, the stability and slow release of carbon sources is achieved, the excellent water quality is ensured, and the production cost is reduced.

CN119371008BActive Publication Date: 2025-05-02JIANGXI JIANHENG ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411830280.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-05-02
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

In traditional sewage treatment, insufficient carbon source will lead to unstable denitrification process, affecting the quality of the effluent water, and the existing composite carbon source has low cost performance and cannot control the carbon source release rate.

Method used

A composite carbon source with a three-layer core-shell structure is used. The outer shell layer is polyvinyl alcohol/corn coin powder composite material, the inner shell layer is corn starch/polyvinyl alcohol/corn coin powder composite material, and the core layer is activated carbon-loaded chitosan material. This structure achieves the stable and slow release of the carbon source.

Benefits of technology

The stable release of carbon sources is achieved, the risk of COD exceeding the effluent COD in the sewage treatment facility effluent is reduced, the clarity of water quality is ensured, and the preparation process is simple and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005185387200000061
    Figure BDA0005185387200000061
  • Figure BDA0005185387200000071
    Figure BDA0005185387200000071
Patent Text Reader

Abstract

The invention discloses a composite carbon source for sewage treatment and a preparation method thereof, belonging to the technical field of sewage treatment. The composite carbon source is a three-layer core-shell structure, wherein the outer shell is a polyvinyl alcohol / corn cob powder composite material, the inner shell is a corn starch / polyvinyl alcohol / corn cob powder composite material, and the core layer is an activated carbon-loaded chitosan material. The outer shell is mixed with polyvinyl alcohol and corn cob powder to reduce the contact area between corn cob powder and sewage treatment bacteria, inhibit the rapid release of the carbon source in the initial stage of corn cob powder, and achieve the wrapping of the kernel; the inner shell is a corn starch / polyvinyl alcohol / corn cob powder composite material, wherein the corn starch can replenish the carbon source in time relative to the corn cob powder, and the corn cob powder can also continuously provide the carbon source; the chitosan in the core layer can provide the necessary carbon source on the one hand, and the adsorption material formed with the activated carbon on the other hand can adsorb impurities in the water, have a flocculation and precipitation effect, and ensure the clarity of the water quality in the later stage of denitrification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sewage treatment, and in particular relates to a composite carbon source for sewage treatment and a preparation method thereof. Background Art

[0002] In recent years, eutrophication of water bodies has become a serious environmental problem. Among many municipal sewage treatment processes, biological nitrification and denitrification processes are widely used in sewage denitrification treatment due to their low cost and high efficiency. Traditional biological denitrification processes are mainly divided into nitrification and denitrification processes. Among them, the denitrification process refers to the process in which heterotrophic denitrifying bacteria use organic carbon sources as electron donors to reduce nitrite nitrogen and nitrate nitrogen produced during nitrification into gaseous nitrogen in an anaerobic environment. Organic carbon sources are important substances in the denitrification process. Their types and the C / N ratio in sewage affect the effect of denitrification. Only by ensuring that there is sufficient carbon source in the water body can the denitrification process proceed smoothly. Insufficient carbon sources will make it difficult for the effluent quality of the sewage treatment plant to meet the standards. At this time, it is necessary to supplement composite carbon sources to promote the stable operation of the system.

[0003] The carbon sources used in wastewater treatment are generally considered to be carbon-containing elements that are easily utilized by microorganisms and nutrients that promote microbial growth. They are often referred to as short-chain, carbon-containing organic matter with simple molecular structures, such as monosaccharides, polysaccharides, oils and fats, organic acids, esters and small molecule alcohols.

[0004] Among them, sugar substances represented by glucose have good denitrification effects as external carbon sources. However, as multi-molecular compounds, sugars are easily used as carbon sources by bacteria, which causes bacteria to multiply in large numbers, leading to sludge expansion, increasing the COD value in the effluent, and affecting the effluent quality. With the improvement of sewage denitrification requirements, the demand for the production of non-toxic and harmless and cost-effective carbon sources has increased. Agricultural waste is rich in natural cellulose and hemicellulose substances and is a good solid slow-release carbon source. However, agricultural waste has a similar release pattern. As time goes by, the carbon release of the waste gradually increases, and the carbon release rate has an obvious feature of first fast and then slow. In practical applications, if no measures are taken, the carbon source released rapidly in the initial stage of agricultural waste will cause the COD of the effluent of sewage treatment facilities to exceed the standard.

[0005] A Chinese invention patent with application number CN202311651621.1 discloses a composite carbon source for sewage treatment and a preparation method thereof. Polyvinyl alcohol is cross-linked with 2-(1-phenyl-2-sulfopropyl) pentanedioic acid, and then composited with treated plant materials and modified graphene to obtain a composite carbon source. The treated plant material is used as a carbon donor, and the cross-linked and composite-modified polyvinyl alcohol is used as a skeleton material. The prepared composite carbon source can adapt to more complex hydraulic conditions, but the price of graphene itself is relatively high, and the composite carbon source has a low cost-effectiveness, and does not have the ability to control the rate of carbon source release according to the characteristics of bacterial growth in different stages of denitrification. Summary of the invention

[0006] The object of the present invention is to provide a composite carbon source for sewage treatment and a preparation method thereof, which can ensure stable release of the carbon source while having a simple preparation process and low cost.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] The invention provides a composite carbon source for sewage treatment. The carbon source has a three-layer core-shell structure, wherein the outer shell layer is a polyvinyl alcohol / corn cob powder composite material, the inner shell layer is a corn starch / polyvinyl alcohol / corn cob powder composite material, and the core layer is an activated carbon-loaded chitosan material.

[0009] The main components of corncob include cellulose, hemicellulose and lignin.

[0010] Furthermore, the thickness of the outer shell layer is 0.3-0.5 mm; the thickness of the inner shell layer is 0.5-0.8 mm.

[0011] The present invention also provides a method for preparing a composite carbon source for sewage treatment, comprising the following steps:

[0012] Step 1, chitosan is dissolved in acetic acid solution to form a 0.1-0.5wt% chitosan solution, the concentration of the acetic acid solution is 0.3-0.5wt%, spherical activated carbon is placed in the chitosan solution, stirred at 30-40°C for 2.5-5h, cooled and washed to neutral, and dried to obtain an activated carbon-loaded chitosan material;

[0013] Step 2: dissolving corn starch in water to form a starch solution, completely dissolving polyvinyl alcohol in water at 90-100° C. to form a PVA solution, uniformly mixing the starch solution and the PVA solution to form a mixed solution, heating to 90-100° C. and stirring for 2-10 minutes, adding corn cob powder to the mixed solution and continuing to stir for 5-10 minutes to obtain a secondary mixed solution, adding glutaraldehyde, and cross-linking reaction for 20-40 minutes, adding activated carbon-loaded chitosan material, stirring and mixing, so that the surface of the activated carbon-loaded chitosan material is completely coated, and after drying, an inner shell layer is formed on the surface to obtain a semi-finished product;

[0014] Step 3: dissolve polyvinyl alcohol in water at 90-100° C. to form a PVA solution, add corn cob powder and stir evenly to obtain a mixture, add the semi-finished product, and after mixing, wrap the mixture on the surface of the semi-finished product, take out and dry the mixture to form an outer shell layer to obtain a composite carbon source.

[0015] Furthermore, the diameter of the spherical activated carbon is 0.5-10 mm.

[0016] Furthermore, in step 1, the spherical activated carbon is placed in a chitosan solution at a mass ratio of spherical activated carbon to chitosan of 50-100:1.

[0017] Furthermore, in step 2, the mass concentration of corn starch in the mixed solution is 3-5 g / mL;

[0018] The mass concentration of polyvinyl alcohol in the mixed solution is 4-5 g / mL;

[0019] The corncob powder is prepared by crushing and sieving corncobs, and has a diameter of 20-50 μm. The mass ratio of the corncob powder to corn starch in the secondary mixed solution is 1-2:1.

[0020] Furthermore, in step 2, the glutaraldehyde is a glutaraldehyde solution with a solid content of 25%, and glutaraldehyde is added to the secondary mixed solution at a volume fraction of 0.5-0.6%.

[0021] Furthermore, in step 2, the mass ratio of the activated carbon-loaded chitosan material to the secondary mixed solution is 0.5-0.8:5.

[0022] Furthermore, in step three, the mass fraction of polyvinyl alcohol in the mixture is 6-10wt%; the mass fraction of corn cob powder in the mixture is 5-15wt%.

[0023] Furthermore, in step three, the mass ratio of the semi-finished product to the mixed material is 1-1.3:20.

[0024] Beneficial effects of the present invention:

[0025] The composite carbon source of the three-layer core-shell structure provided by the present invention comprises an outer shell layer of a polyvinyl alcohol / corn cob powder composite material, and the contact area between the corn cob powder and the sewage treatment bacteria is reduced by mixing the polyvinyl alcohol and the corn cob powder, thereby inhibiting the rapid release of the carbon source of the corn cob powder in the initial stage, and wrapping the inner shell with the film-forming property of the polyvinyl alcohol, thereby realizing the slow release of the carbon source in the inner shell; as denitrification proceeds, the number of microorganisms increases continuously, and the inner shell layer is gradually exposed after the outer shell layer is degraded, and the inner shell layer is a corn starch / polyvinyl alcohol / corn cob powder composite material, wherein the corn starch is more easily utilized as a carbon source than the corn cob powder, and the carbon source can be replenished in time, and the corn cob powder can also continuously provide the carbon source; in the later stage, the denitrifying bacteria will be over-reproduced under the catalysis of the carbon source, and a large number of corpses of the denitrifying bacteria that have ended their life cycle will float in the water, damaging the water quality, and at this time the core layer is exposed, and the chitosan in the activated carbon-loaded chitosan material can provide the necessary carbon source on the one hand, and the adsorption material formed with the activated carbon can adsorb impurities in the water on the other hand, and has a flocculation and precipitation effect, thereby ensuring the clarity of the water quality. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] This embodiment provides a composite carbon source for sewage treatment. The composite carbon source is a three-layer core-shell structure, wherein the outer shell is a polyvinyl alcohol / corn cob powder composite material, the inner shell is a corn starch / polyvinyl alcohol / corn cob powder composite material, and the core layer is an activated carbon-loaded chitosan material. The specific preparation method is as follows:

[0029] Step 1, chitosan is dissolved in acetic acid solution to form a 0.5wt% chitosan solution, the concentration of the acetic acid solution is 0.5wt%, spherical activated carbon with a diameter of 0.5-10mm is placed in the chitosan solution, the mass ratio of spherical activated carbon to chitosan is 50:1, stirred at 30°C for 5h, cooled and washed to neutral, and dried to obtain an activated carbon-loaded chitosan material;

[0030] Step 2: dissolving corn starch in water to form a starch solution, and completely dissolving polyvinyl alcohol in water at 90-100° C. to form a PVA solution. The starch solution and the PVA solution are evenly mixed to form a mixed solution, wherein the mass concentration of corn starch in the mixed solution is 3 g / mL, and the mass concentration of polyvinyl alcohol is 4 g / mL. The solution is heated to 90° C. and stirred for 5 minutes. Corn cob powder (prepared by crushing and sieving corn cobs, with a diameter of 20-50 μm) is added to the mixed solution, and the stirring is continued for 10 minutes to obtain a secondary mixed solution, wherein the mass ratio of corn cob powder to corn starch in the secondary mixed solution is 1:1, and a glutaraldehyde solution with a solid content of 25% is added, wherein the volume fraction of the glutaraldehyde solution is 0.5%, and the cross-linking reaction is carried out for 20 minutes. Activated carbon-loaded chitosan material is added, and the mass ratio of the activated carbon-loaded chitosan material to the secondary mixed solution is 0.5:5. The mixture is stirred and mixed to completely coat the surface of the activated carbon-loaded chitosan material, and an inner shell layer with a thickness of 0.5-0.8 mm is formed on the surface after drying to obtain a semi-finished product.

[0031] Step three, dissolve polyvinyl alcohol in water at 900°C to form a PVA solution, add corn cob powder and stir evenly to obtain a mixture, the mass fraction of polyvinyl alcohol in the mixture is 6wt%, the mass fraction of corn cob powder is 5wt%, add semi-finished products, the mass ratio of the semi-finished products to the mixture is 1:20, after mixing, the mixture is wrapped on the surface of the semi-finished products, and after taking out and drying, the mixture forms an outer shell layer with a thickness of 0.3-0.5mm to obtain a composite carbon source.

[0032] Example 2

[0033] The only difference from Example 1 is that in step 3, the mass fraction of polyvinyl alcohol in the mixture is adjusted to 8wt%, and the mass fraction of corn cob powder is adjusted to 10wt%. Other conditions and steps are the same as in Example 1.

[0034] Example 3

[0035] The only difference from Example 1 is that in step 3, the mass fraction of polyvinyl alcohol in the mixture is adjusted to 10wt%, and the mass fraction of corn cob powder is adjusted to 15wt%. Other conditions and steps are the same as in Example 1.

[0036] Example 4

[0037] The only difference from Example 2 is that in step 2, the mass concentration of corn starch in the mixed solution is adjusted to 4 g / mL, and the other steps and conditions are the same as in Example 2.

[0038] Example 5

[0039] The only difference from Example 2 is that in step 2, the mass concentration of corn starch in the mixed solution is adjusted to 5 g / mL, and the other steps and conditions are the same as in Example 2.

[0040] Example 6

[0041] The only difference from Example 4 is that in step 1, the mass ratio of spherical activated carbon to chitosan is 80:1, and the other steps and conditions are the same as Example 4.

[0042] Example 7

[0043] The only difference from Example 4 is that in step 1, the mass ratio of spherical activated carbon to chitosan is 100:1, and the other steps and conditions are the same as Example 4.

[0044] Comparative Example 1

[0045] Compared with Example 1, the core layer of the composite carbon source provided in this comparative example is an activated carbon material without loading chitosan, and the other steps and conditions are the same as those in Example 1.

[0046] Comparative Example 2

[0047] Compared with Example 1, the composite carbon source provided in this comparative example does not include an inner shell layer, step 2 is omitted, and the other steps and conditions are the same as in Example 1.

[0048] Comparative Example 3

[0049] Compared with Example 1, the composite carbon source provided in this comparative example does not include an outer shell layer, step three is omitted, and the other steps and conditions are the same as in Example 1.

[0050] The composite carbon sources prepared in Examples 1-7 and Comparative Examples 1-3 were respectively added into 10 denitrification filters in a sewage treatment plant at 5 kg / t / h. Each denitrification filter corresponds to a composite carbon source. The COD of the influent was 81.0 mg / L and the TN was 33.9 mg / L. The COD and total nitrogen concentrations of the effluent were continuously monitored for 24 hours. The results are shown in Table 1:

[0051] Table 1

[0052]

[0053]

[0054] As can be seen from Table 1, in Example 1 and Example 3, the proportion of corn cob powder in the outer shell layer is gradually increased, and the proportion of polyvinyl alcohol is reduced. Since corn cob powder releases a large amount of carbon source in the rapid release period, in the early stage of denitrification, if this part of the carbon source exceeds the utilization amount of the metabolic proliferation process of the denitrifying microorganisms, it will cause the effluent COD to be too high, resulting in excessive effluent and waste of carbon source. In Example 2, an appropriate amount of corn cob powder can improve the total nitrogen removal rate, but the excessive corn cob powder in Example 3 causes COD accumulation in the early and middle stages, and the COD in the effluent is higher than that in Example 2; Example 4-Example 5, on the basis of Example 2, increases the proportion of corn starch in the inner shell layer, among which Example 4 has the best ratio, which can not only supplement the carbon source required for the growth of a large amount of bacteria in the middle stage, but also will not cause high COD; In Example 6-Example 7, the chitosan loading amount of the core layer is increased, and the chitosan loading amount increases. On the one hand, it can ensure the necessary bacterial growth and prevent the late bacteria from dying due to lack of carbon source. On the other hand, it can flocculate and precipitate to reduce the effluent COD, and the effluent water quality in Example 6 is the best. Compared with the embodiment, the lack of different layer structures in comparative examples 1-3 will lead to poor water quality, which is not conducive to sewage treatment.

[0055] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite carbon source for sewage treatment, characterized in that: The composite carbon source is a three-layer core-shell structure, wherein the outer shell is a polyvinyl alcohol / corn cob powder composite material, the inner shell is a corn starch / polyvinyl alcohol / corn cob powder composite material, and the core layer is an activated carbon-loaded chitosan material; The preparation steps of the composite carbon source are as follows: Step 1, chitosan is dissolved in acetic acid solution to form a 0.1-0.5wt% chitosan solution, the concentration of the acetic acid solution is 0.3-0.5wt%, spherical activated carbon is placed in the chitosan solution, stirred at 30-40°C for 2.5-5h, cooled and washed to neutral, and dried to obtain an activated carbon-loaded chitosan material; Step 2: dissolving corn starch in water to form a starch solution, completely dissolving polyvinyl alcohol in water at 90-100° C. to form a PVA solution, uniformly mixing the starch solution and the PVA solution to form a mixed solution, heating to 90-100° C. and stirring for 2-10 minutes, adding corn cob powder to the mixed solution and continuing to stir for 5-10 minutes to obtain a secondary mixed solution, adding glutaraldehyde, and cross-linking reaction for 20-40 minutes, adding activated carbon-loaded chitosan material, stirring and mixing, so that the surface of the activated carbon-loaded chitosan material is completely coated, and after drying, an inner shell layer is formed on the surface to obtain a semi-finished product; Step 3: dissolve polyvinyl alcohol in water at 90-100° C. to form a PVA solution, add corn cob powder and stir evenly to obtain a mixture, add the semi-finished product, and after mixing, wrap the mixture on the surface of the semi-finished product, take out and dry the mixture to form an outer shell layer to obtain a composite carbon source.

2. A composite carbon source for sewage treatment according to claim 1, characterized in that: The thickness of the outer shell layer is 0.3-0.5 mm; the thickness of the inner shell layer is 0.5-0.8 mm.

3. A composite carbon source for sewage treatment according to claim 1, characterized in that: The diameter of the spherical activated carbon is 0.5-10 mm.

4. A composite carbon source for sewage treatment according to claim 1, characterized in that: In step 1, the spherical activated carbon is placed in a chitosan solution at a mass ratio of spherical activated carbon to chitosan of 50-100:

1.

5. A composite carbon source for sewage treatment according to claim 1, characterized in that: In step 2, the mass concentration of corn starch in the mixed solution is 3-5 g / mL; The mass concentration of polyvinyl alcohol in the mixed solution is 4-5 g / mL; The corncob powder is prepared by crushing and sieving corncobs, and has a diameter of 20-50 μm. The corncob powder is added to the mixed solution according to a mass ratio of corncob powder to corn starch = 1-2:

1.

6. A composite carbon source for sewage treatment according to claim 1, characterized in that: In step 2, the glutaraldehyde is a glutaraldehyde solution with a solid content of 25%, and glutaraldehyde is added to the secondary mixed solution at a volume fraction of 0.5-0.6%.

7. A composite carbon source for sewage treatment according to claim 1, characterized in that: In step 2, the mass ratio of the activated carbon-loaded chitosan material to the secondary mixed solution is 0.5-0.8:

5.

8. The composite carbon source for sewage treatment according to claim 1, characterized in that: In step three, the mass fraction of polyvinyl alcohol in the mixture is 6-10wt%; the mass fraction of corn cob powder in the mixture is 5-15wt%.

9. The composite carbon source for sewage treatment according to claim 1, characterized in that: In step three, the mass ratio of the semi-finished product to the mixed material is 1-1.3:20.

Citation Information

Patent Citations

  • A composite carbon source for sewage treatment and preparation method thereof

    CN117658340B

  • Composite carbon source material and preparation method thereof

    CN114409065A

  • Method for preparing nitrogen-removal-enhanced slow-release carbon source filler by using corncob-polycaprolactone powder mixed system

    CN115611432A